The Effect of Red Beans on Increasing HB Levels of Pregnant Women - Nurdiyah Nurdiyah; Selasih Putri Isnawati Hadi; Febry Heldayasari (Jurnal MID-Z (MIDWIFERI ZIGOT), 2023)
Hemoglobin level is a measure to find out whether a person has anemia or not. According to Basic Health Research (Riskesdas) (2021) 48.9% of pregnant women in East Java Province experience anemia with an average prevalence of anemia still below the national target of 28%. Low Hb in pregnant women can cause miscarriage, bleeding, birth defects and others. Red bean is one of the foods that contain minerals that are useful in increasing hemoglobin levels in pregnant women.  The purpose of the study was to analyze the effect of red beans on increasing HB levels of pregnant women at the Bubakan Pacitan Health Center. The esearch method used is quantitative using the One Group Pretest-Postest Design. The subjects of this study were pregnant women in the first to third trimesters and met the criteria. The sample using Nonprobability Sampling obtained 32 respondents. Data analysis used univariate analysis and bivariate analysis with the Paired Sampel T-Test. The results of this research indicate that is a difference before and after consuming red beans on the increase in hemoglobin levels of pregnant women based on the results of the Paired sampel t-test, a significant probability value of 0.000 is obtained where the probability (Asymp.sig <0.05) means the hypothesis is accepted.  There is a difference before and after consuming red beans on the increase in hemoglobin levels of pregnant women at the Bubakan Pacitan Health Center.